Análisis y diseño optimizado de techado de piscina semi olímpica y servicios complementarios – UNSM (TOMO I) - Chavez Tello, Miguel Angel (2008)
The present thesis's project named "ANALYSIS ANO DESIGN OPTIMIZED OF ROOF SWIMMING POOL SEMIOLIMPYC ANO COMPLEMENTARY SERVICES - UNSM" rises as proposal in order to the roofing completely of the Swimming Pool Semiolimpyc - UNSM, project than at present this one in execution and than only consider the roofing of spectator's tribunes, getting interior circulations and the same low swimming pool with the submission ok climatic inclemencias ( rain, sun, etc ), could have generated discomfort and discoordinations in the different planned events for San Martin's University National- T. Another purpose that has the present project, is generating among those concerned the knowledge in sorne aspects of the steel design with the utilization of the LRFD designing methodology (load and Resistance Factor Design), situation that intends to help, having in bill than in the pregrade studies of lngeniería's Faculty of Civil them they acquire knowledge of the steel design through an electiva and non-obligatory course according to the in use currícula. In the present proposal of the roofing swimming pool semiolirnpyc and his complernentary services, they executed works on the following lines: In the first time, its initiated the works with the evaluation of the project's architecture original, analisysing the possible roofing proposals, permitting to establish geornetry, the area to roof, structure's possible cambers, the roofing height, etc. Simultaneous manner, it has happened to me that bibliography of different authors and consulting specialists in the theme, permitting to establish criteria in order to reasonable solutions in our proposal has been checked. In the second time, proceeded from to the organizing the information, analysis and design of the model proponed; in this stage worked with help to the Software Structural SAP 2000, its permitted accomplishing them analysis 3,829 elernents Frarne, 410 elements joint y with help of 3,504 element type shell of our modeling in 30. ls propitious mentioning, than the analysis is propitious tried possible representativa, he is hence to have the fact realized in 30, with loads determinad in the 3 directions to act at the same time according to the design's code. Finally and in the third position, proceeded from to the dimensionamiento detailed of the system•s elements, elaboration diagrams and the final detail. For a best development has divided the structure of thesis•s Project in 8 chapters distributed the following manner: CHAPTER 1: encounters general lntroduction to the project, the situational frame considering all the necessary aspects in order toan optimal study, said information will permit to do a guessed analysis in order to the later definition to us and the alternative's selection but convenient prop the system once was projected. CHAPTER 11: they detail all the theoretic foundation that the analysis's all of the parameters and design in steel, with graphic performances that make easy the same one's understanding have a base. CHAPTER 111: they consider the materials and methods as tools of the present document's elaboration specifying the technical criteria in the respective designs. CHAPTER IV: The studies gutted realizad and detail aftermaths themselves varied designs. ls important Specifying the utilization of the draws or pictures of the designing Manual of the LRFD, the same ones than present in imageries of the original version in English. CHAPTER V: gutted in the chapter discuss aftermaths themselves previous. CHAPTER VI: he contains the conclusions obtained after all the analysis and process of the elaboration of the present project in order to after to propose respective recomrnendations. CHAPTER VIl: Contemplate the bibliographic references utilizad in the present project in order that the applicant may enlarge conceptual knowledge realizad. CHAPTER VIII annexes complementary information of the present project.